Dampak Kemajuan Pendidikan terhadap munculnya Fenomena Juken Jigoku (Neraka Ujian Masuk) di Jepang - Sri Dewi Adriani (Humaniora, 2010)
Japan is one of one of the developed countries in the world having an advance standard of education. People have been aware of its importance. Besides, the government has been fully supporting the development of education in the society. Everyone has been respected by their educational achievement. This condition causes of strain to the younger generation especially for those who are going to enter to the prominent universities. This condition is so called Juken Jigoku which is lexically translated as hell of entrance examination